Interplay between gut microbiota and acute kidney injury: a review of their mutual influence and causation - Niroj Mali; Saroj Mali; Ling Zhang; Ping Fu (Renal Failure, 2025)
It is unclear, therefore, exactly how gut microbes and renal processes communicate. Recent developments in the field of microbiome research present chances to enhance our comprehension and management of acute kidney injury (AKI). This review highlights important ideas and suggests more research while giving a general summary of the microbiome’s influence on kidney function and AKI. AKI is a complex condition that develops through a variety of pathways. Recent experimental research has highlighted the important role that the gut microbiota plays in the course of AKI. Our understanding of human biology has been completely transformed by the current increase in gut microbiota research. Amazing progress in DNA sequencing analysis, especially in the areas of metagenomics and metatranscriptomics, has greatly increased our ability to measure and track complex microbial populations. As such, we are now in a better position to look at how these communities affect human health and illness. As a result, the relationships between renal physiology and pathophysiology and the gut microbiota are now better understood. Both experimental AKI and chronic renal illness have been linked to changes in the intestinal microbiome. This succinct review attempts to examine our present knowledge of the immune-modulatory effects of the gut microbiota, how kidney disorders are influenced by it, and the possible reciprocal interaction between kidney diseases and the microbiota. Subsequent investigations ought to concentrate on delving deeper into the function of the gut microbiota in renal disorders and finding possible therapeutic strategies for adjusting it.